2021
DOI: 10.1182/blood.2020010167
|View full text |Cite
|
Sign up to set email alerts
|

Intact TP-53 function is essential for sustaining durable responses to BH3-mimetic drugs in leukemias

Abstract: Selective targeting of BCL2 with the BH3-mimetic venetoclax is proving transformative for patients with various leukemias. TP53 controls apoptosis upstream from where BCL2 and its pro-survival relatives, such as MCL1, act. Therefore, targeting these pro-survival proteins could trigger apoptosis across diverse blood cancers, irrespective of TP53 mutation status. Indeed, targeting BCL2 has produced clinically relevant responses in blood cancers with aberrant TP53. However, we show that TP53 mutated or deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 43 publications
2
91
0
Order By: Relevance
“…18 , 41 Elegant preclinical models have demonstrated that this outgrowth of TP53-mutant clones occurs when venetoclax is used alone as well as in combination with cytarabine or decitabine. 41 However, when venetoclax is combined with an MCL-1 inhibitor (but not when an MCL-1 inhibitor is used alone or with cytarabine or decitabine), both TP53-mutant and wild-type clones can be eradicated, providing a novel potential approach for treating patients with TP53-mutated AML. 41 The etiology of this synergy between combined BCL-2 and MCL-1 inhibition in TP53-mutated AML remains unclear, although it may be attributable to decreased priming for intrinsic apoptosis in TP53-mutated cells, thereby requiring inhibition of multiple antiapoptotic proteins to prevent the eventual outgrowth of a resistant clone during sublethal inhibition of BCL-2 or MCL-1.…”
Section: Resistance To Venetoclaxmentioning
confidence: 99%
See 2 more Smart Citations
“…18 , 41 Elegant preclinical models have demonstrated that this outgrowth of TP53-mutant clones occurs when venetoclax is used alone as well as in combination with cytarabine or decitabine. 41 However, when venetoclax is combined with an MCL-1 inhibitor (but not when an MCL-1 inhibitor is used alone or with cytarabine or decitabine), both TP53-mutant and wild-type clones can be eradicated, providing a novel potential approach for treating patients with TP53-mutated AML. 41 The etiology of this synergy between combined BCL-2 and MCL-1 inhibition in TP53-mutated AML remains unclear, although it may be attributable to decreased priming for intrinsic apoptosis in TP53-mutated cells, thereby requiring inhibition of multiple antiapoptotic proteins to prevent the eventual outgrowth of a resistant clone during sublethal inhibition of BCL-2 or MCL-1.…”
Section: Resistance To Venetoclaxmentioning
confidence: 99%
“…41 However, when venetoclax is combined with an MCL-1 inhibitor (but not when an MCL-1 inhibitor is used alone or with cytarabine or decitabine), both TP53-mutant and wild-type clones can be eradicated, providing a novel potential approach for treating patients with TP53-mutated AML. 41 The etiology of this synergy between combined BCL-2 and MCL-1 inhibition in TP53-mutated AML remains unclear, although it may be attributable to decreased priming for intrinsic apoptosis in TP53-mutated cells, thereby requiring inhibition of multiple antiapoptotic proteins to prevent the eventual outgrowth of a resistant clone during sublethal inhibition of BCL-2 or MCL-1. 41 Trials assessing the combination of BCL-2 and MCL-1 inhibitors are currently ongoing for patients with AML, including an international phase Ib study assessing venetoclax + the MCL-1 inhibitor S64315 (NCT03672695).…”
Section: Resistance To Venetoclaxmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Identifying resistance factors to venetoclax therapy is therefore an area of great clinical relevance. Whilst CRISPR gene knock-out screens have identi ed TP53 loss and other factors that are mediators of venetoclax resistance, 20,21 no studies have utlised CRISPRa to investigate genes that can confer venetoclax resistance when upregulated from their endogenous promoters. Cell lines derived from the CRISPRa mouse model of DHL that are highly sensitive to venetoclax provide an ideal platform to perform genome-wide CRISPRa screens for identifying resistance factors.…”
Section: Introductionmentioning
confidence: 99%
“…
In this issue of Blood, Thijssen et al report that leukemia or lymphoma cells with TP53 loss have a selective advantage over time when treated with sublethal doses of a BCL-2 or MCL-1 inhibitor, because of reduced activation of BAX and BAK, but this defect can be overcome with dual treatment with both inhibitors. 1
…”
mentioning
confidence: 99%